Safety, Tolerability, and Efficacy of Pain Reduction by Gabapentin for Acute Headache and Meningismus After Aneurysmal Subarachnoid Hemorrhage: A Pilot Study - Dhakal, Laxmi P.; Turnbull, Marion T.; Jackson, Daniel A.; Edwards, Emily; Hodge, David O.; Thottempudi, Neeharika; Kamireddi, Prasuna; Akinduro, Oluwaseun O.; Miller, David A.; Meschia, James F.; Freeman, William D. (Frontiers in Neurology, 2020)
Introduction: Severe, often sudden-onset headache is the principal presenting symptoms of aneurysmal subarachnoid hemorrhage (aSAH). We hypothesized that gabapentin would be safe and tolerable for aSAH-induced headaches and would reduce concurrent opioid use. Methods: We performed a single-center, double-blind, randomized, placebo-controlled trial (registered at ClinicalTrials.gov; NCT02330094) from November 24, 2014, to June 24, 2017, where aSAH patients received either dose-escalating gabapentin or oral placebo, both alongside a standard of care pain regimen. After 7 days, patients had the option to continue in an open-label period until 14 days after enrollment or until discharge from the intensive care unit. Our primary endpoint was the efficacy of gabapentin in reducing headache numeric pain scores and opioid usage in patients with aSAH compared to the placebo group. We identified 63 potential patients with aSAH for the study. After applying stringent exclusion criteria, 16 eligible patients were enrolled into one of two arms. Results: The study ended prematurely after reaching a pre-specified funding period and an unexpected drop in aSAH cases. There was a trend toward lower headache numeric pain scores and opioid use in the gabapentin treated arm; however this was not significantly different. Gabapentin was well tolerated by participants and no adverse effects were reported. Conclusions: While there was a trend toward lower pain scores and opioid requirement in the gabapentin group, the study was underpowered to detect a difference. Larger multicenter trials are required to evaluate the efficacy of gabapentin to reduce opioid requirements after aSAH.